Determinants of Organisational Commitment among Employees Aged 50+ - Kędra, Michał; Sobotka, Bartosz; Muda, Rafał; Leoniak, Krzysztof; Hamerski, Damian (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: The aim of the study was to identify differences in affective and continuance commitment among employees aged 50 and above, based on their demographic characteristics and job positions within the organisation.Research Design & Methods: A study was conducted among employees aged 50+ in the Polish market who work in various full-time positions. Participants reported their socio-demographic characteristics, answered questions related to their job and history of job changes. Additionally, they responded to the Organisational Commitment Scale.Findings: The results revealed that emotional commitment varies depending on the job position and the type of work performed. However, working in different positions differentiates continuance commitment. No differences were observed between men and women in both types of attachment.Implications / Recommendations: The research results provide practical insights for individuals involved in recruiting, hiring, and collaborating with employees aged 50+.Contribution: Knowledge about various aspects of organisational commitment allows for better job customisation and the maximisation of employee potential.